APPLICATION OF HYDROPHOBIC CEMENT SLURRIES «RAN-M» OF «RAMSINKS-2M» GROUP TO AVOID FLUID KICK - Nalyvaiko, O. I.; Melnikov, O. L.; Nalyvaiko, L. G.; Petrash, R. V.; Khivrenko, V. N. (Academic journal Industrial Machine Building Civil Engineering, 2018)
Laboratory studies of cement slurry and cement stone is established that hydrophobic cement slurry «RAN-M» consists of NTPha additives for well cements PTC-1-100 and «Ramsinks-2M». In the laboratory confirmed the technical parameters of the newest hydrophobic cement slurries (mobility, density, separation, pumpability, etc.) according to the standard requirements in the respective devices. Done such works as: implementation of the selection of formulations of cement slurries with different rate of strength development for different temperature integrals.